Review on stroke induced depression - G., Ramya Balaprabha; P., Sri Vaishnavi; N., Krishna Sree; M., Harika Guptha; T., Rama Rao (International Journal of Research in Medical Sciences, 2024)
One of the frequent and dangerous aftereffects of stroke is post-stroke depression (PSD). About one in three stroke survivors had depression following their stroke. It had a significant impact on functional recovery, which resulted in a low standard of living. Even worse, there is a clear correlation between it and a high death rate. Our goal in doing this evaluation was to come up with a thorough and cohesive knowledge of PSD based on both recently released research and well-known works. We discovered that the incidence of PSD varies from 11 to 41% within a two-year period, based on a significant number of researches. The severity of the stroke, the location of the lesion, past history of depression, and other factors all has a role in the development of PSD. The DSM criteria are currently the primary basis for diagnosing PSD, and they are often coupled with different depression scales. However, there isn’t a single, cohesive process that explains PSD which now include aberrant neurotrophic response, elevated inflammatory markers, lowered monoamine levels, glutamate-mediated excitotoxicity, and dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis. Pharmacotherapy and psychosocial therapies are currently used in the treatment of PSD. Even though researchers have made significant progress, many problems still need to be solved. In particular, the PSD’s mechanism is not entirely understood.